Client assignment problems for distributed interactive computing - Zhang, Lu (2013)
The steady growth in broadband Internet accesses and PC penetration is leading to a shift in emphasis from individual computers to distributed interactive computing that allows multiple participants at different locations to interact with each other in real time. Recent years have witnessed rapid development of Distributed Interactive Applications (DIAs) in many areas such as interactive digital media and entertainment, distributed interactive simulation, and collaborative computer-aided design and engineering. Interactivity is a primary performance measure of DIAs owing to their human-in-the-loop nature. To support graceful interactions, it is required that when a participant of the DIA performs an operation, other participants are able to see the effect of the operation quickly. Network latency is a major barrier to propagating and reflecting the effects of operations timely. Wide geographical spreads of participants in large-scale DIAs necessitate distributed deployment of servers to combat network latency and achieve high interactivity. In a distributed server architecture, the interactivity performance depends not only on client-to-server latencies but also interserver latencies. Meanwhile, the consistency and fairness requirements of DIAs, which are important to providing pleasant user experiences, may introduce artificial synchronization delays in the interaction that can also influence the interactivity performance. All these factors are directly affected by how the clients are assigned to the servers.